PENERAPAN SISTEM KEAMANAN MENGGUNAKAN CRYPTOGRAPHY PADA APLIKASI CHATTING DENGAN MEMODIFIKASI ALGORITMA RIVEST SHAMIR ADLEMAN (RSA) - Muttaqin Muttaqin; Haruno Sajati; Nurcahyani Dewi Retnowati (Institut Teknologi Dirgantara Adisutjipto, 2014)
Chatting application is an application which used for communication through local network or internet. It can use to make communication to be effective and easy to use but there are several shortage in delivery information process is data security when communication is going on. Using chrypthography with modification Rivest Shamir adleman (RSA) algorithm in encryption process and decryption on packet data which transmited is one of security system which can used in this application then the security of data packet secured. Result from implementation of chatting application which apply chrypthography with modification Rivest Shamir adleman (RSA) algorithm have done in local network and internet able to run smoothly and have done by several testing cases based on certain scenario. Whereas process testing encryption and decryption using tools wireshark.